Replication of Associations of Genetic Loci Outside the HLA Region With Susceptibility to Anti–Cyclic Citrullinated Peptide–Negative Rheumatoid Arthritis. Issue 7 (July 2016) - Viatte, Sebastien; Massey, Jonathan; Bowes, John; Duffus, Kate; Eyre, Stephen; Barton, Anne; Worthington, Jane
Abstract : Objective: Genetic polymorphisms within the HLA region explain only a modest proportion of anti–cyclic citrullinated peptide (anti‐CCP)–negative rheumatoid arthritis (RA) heritability. However, few non‐HLA markers have been identified so far. This study was undertaken to replicate the associations of anti‐CCP–negative RA with non‐HLA genetic polymorphisms demonstrated in a previous study. Methods: The Rheumatoid Arthritis Consortium International densely genotyped 186 autoimmune‐related regions in 3, 339 anti‐CCP–negative RA patients and 15, 870 controls across 6 different populations using the Illumina ImmunoChip array. We performed a case–control replication study of the anti‐CCP–negative markers with the strongest associations in that discovery study, in an independent cohort of anti‐CCP–negative UK RA patients. Individuals from the arcOGEN Consortium and Wellcome Trust Case Control Consortium were used as controls. Genotyping in cases was performed using Sequenom MassArray technology. Genome‐wide data from controls were imputed using the 1000 Genomes Phase I integrated variant call set release version 3 as a reference panel. Results: After genotyping and imputation quality control procedures, data were available for 15 non‐HLA single‐nucleotide polymorphisms in 1, 024 cases and 6, 348 controls. We confirmed the known markers ANKRD55 (meta‐analysis odds ratio [OR] 0.80; P  = 2.8 × 10 −13 ) and BLK (OR 1.13; P  = 7.0 × 10 −6 ) and identified new and specific markers of anti‐CCP–negative RA (prolactin [ PRL ] [OR 1.13; P  = 2.1 × 10 −6 ] and NFIA [OR 0.85; P  = 2.5 × 10 −6 ]). Neither of these loci is associated with other common, complex autoimmune diseases. Conclusion: Anti‐CCP–negative RA and anti‐CCP–positive RA are genetically different disease subsets that only partially share susceptibility factors. Genetic polymorphisms located near the PRL and NFIA genes represent examples of genetic susceptibility factors specific for anti‐CCP–negative RA.